PERAN SATUAN POLISI PAMONG PRAJA DALAM MENERTIBKAN MINUMAN BERALKOHOL DI KABUPATEN INDRAMAYU PROVINSI JAWA BARAT - Restu Agung Firdaus; Hasna Azmi Fadhilah (Jurnal Tatapamong, 2020)
Problems regarding the role of the Civil Service Police Unit which are not running optimally so that it has an impact on peace and public order, namely the discovery of traders and consumers of alcoholic beverages due to lack of socialization and operations often used by traders and consumers to continue to circulate and consume. In connection with the research analysis, the authors use the theory of Biddle and Thomas. While the method used is descriptive qualitative. The data collection techniques used by interview, documentation and observation. From the results of the study, it was found that the Civil Service Police Unit was not optimal in carrying out its role. One of them is the enforcement of regional laws and regulations, which is still found abuse of alcoholic beverages, with indicators of weak supervision and weak faith of the people of Indramayu Regency itself. The efforts that have been made by the Indramayu Regency Civil Service Police Unit are through the development of members, the formation of Civil Servant Investigators, capacity building of employees, and supporting physical facilities.